IMPACT OF SEVERITY OF COVID-19 ON HAEMATOLOGICAL PARAMETERS IN PATIENTS REPORTING TO SAIDU GROUP OF TEACHING HOSPITALS, SWAT - Saeed, Javeria; Lal, Amreek (Journal of Ayub Medical College Abbottabad, 2023)
Background: In 2019 novel coronavirus was discovered in Wuhan, China and declared pandemic by world health organization. The disease caused by this virus called coronavirus disease 2019 (COVID-19). Among the corona family the actual virus responsible for COVID-19 is Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2). Objective of the study was to determine the pattern of blood parameters in corona virus disease (COVID-19) positive cases and the association of these parameters with severity of COVID-19. Method: This cross-sectional descriptive study was conducted on 105 participants who were confirmed positive by SARS-CoV-2 through real-time reverse transcriptase PCR, both genders, and Pakistani nationals. The participants who were below 18 years age and missing data were excluded. Haemoglobin (Hb), total leukocyte count (TLC), neutrophil, lymphocyte, monocyte, basophil and eosinophil counts were calculated. Comparison of blood parameters was done among various severity classes of COVID-19 by running one way ANOVA. The level of significance was p‰¤0.05. Results: The mean age of the participants was 50.6±6.26 years. Males were 78(74.29%) and females were 27(25.71%). In critical type COVID-19 the mean haemoglobin was least (10.21±1.07 g/dl) and highest in mild cases (15.76±1.16 g/dl) and these differences were highly statistically significant (p<0.001). TLC was highest in critical COVID cases (15.90±0.51x 103/Î¼l) followed by moderate (12.44±0.65x103/Î¼l). Similarly, neutrophil count was highest in critical (89±2.1) followed by severe (86±1.12). Conclusion: There is significant decrease in mean haemoglobin level and platelet count but increase in TLC in patients infected from COVID-19.